2017
DOI: 10.3892/etm.2017.4809
|View full text |Cite
|
Sign up to set email alerts
|

Effects of telmisartan on improving leptin resistance and inhibiting hepatic fibrosis in rats with non-alcoholic fatty liver disease

Abstract: Abstract. The present study aimed to investigate the impacts of telmisartan (TEL) on hepatic fibrosis, serum leptin, leptin protein in liver tissue and its mRNA expression level in rats with non-alcoholic fatty liver disease (NAFLD). Male Sprague Dawley rats were randomly divided into the control (N), model (M), polyene phosphatidylcholine (P) and TEL (T) groups. Group M and the intervention groups were given a high-fat diet for 12 weeks to induce NAFLD, followed by 4 weeks of intragastric administration of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The mean value of NFS was significantly increased in Group I while it remained stable in Group II, which indicated that telmisartan prevented the progression of liver fibrosis. This observation confirmed previous studies that showed telmisartan had antifibrotic effect (15,33,34). The antifibrotic effect of telmisartan is associated with suppression of inflammasome maturation by evidence of a significant decrease of serum levels of IL-1β and Il-18.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The mean value of NFS was significantly increased in Group I while it remained stable in Group II, which indicated that telmisartan prevented the progression of liver fibrosis. This observation confirmed previous studies that showed telmisartan had antifibrotic effect (15,33,34). The antifibrotic effect of telmisartan is associated with suppression of inflammasome maturation by evidence of a significant decrease of serum levels of IL-1β and Il-18.…”
Section: Discussionsupporting
confidence: 93%
“…It suppressed the expressions of C-reactive protein (CRP) IL-1β, IL-6, and TNF-α in the experimental animal model of acute colitis and acute myocardial infarction (13,14). Telmisartan reduced the fibrosis liver score in rats fed with high fat diet for three months, which represented an animal model of NAFLD, by suppressing the expression of leptin in the liver (15). In the murine NASH model, telmisartan delay the progression of steatohepatitis by complex mechanisms including anti-inflammatory (as it suppressed macrophage infiltration into the liver), and anti-adiposity like effect (16).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, HF animals treated with losartan or telmisartan benefited from AT1r blockade, as they favored the ACE2/MASr axis over the ACE1/AT1r axis, which has been previously associated with the amelioration of glucose intolerance, hepatic inflammation, and prevention of steatosis and fibrosis[8,15,20]. The RAS modulation by telmisartan can explain previous beneficial effects on the livers of an animal model of hepatic fibrosis[27] and in human with steatohepatitis[28], without side effects. Although the HF diet did not induce fibrosis, our results show that the AT1R blockade reduced PLIN 2 expression and hepatic triacylglycerol levels, both of which are strongly correlated with reduced hepatic steatosis[11,29].…”
Section: Discussionmentioning
confidence: 99%
“…Polyene phosphatidylcholine (PPC) is a hepatoprotective agent, which has been widely used to treat various types of hepatopathy such as viral hepatitis, liver damage or nonalcoholic steatohepatitis [25][26][27][28]. The drug can be extracted from soy and rich in polyunsaturated fatty acids [29].…”
Section: Introductionmentioning
confidence: 99%